La mejor manera de cuantificar la ventaja de jugar en casa en deportes de equipo: una investigación con ligas de Balonmano senior masculino en Portugal y España - Matos, R. M.; Amaro, N.; Pollard, R. (Revista Internacional de Ciencias del Deporte, 2020)
Home advantage (HA), or the effect of match location, has been shown to play an important role in determining the result of a game. A method introduced over 30 years ago has enjoyed wide use. However, there is a possible problem with its interpretation. Although this can be overcome by rescaling the original value for HA, this paper introduces a somewhat different approach to quantifying HA, one that is derived by expressing home performance specifically as a function of away performance. The various methods are illustrated by analyzing HA for teams in the men`s professional handball leagues in Portugal and Spain for the 2016-17 season. Results show that the traditional and rescaled methods both ensure a maximum value of 100% for HA, while the new method can produce values well above 100%. Also, when HA is small, as in the case of goals scored and conceded, then values from the new method are about twice those from the rescaled method. However, when HA is larger, as in the case of most of the teams in the lower half of the Spanish league table, when based on points, the new method produces HA values which are much higher that the rescaled. This method provides a new dimension to considerwhen trying to quantify HA. It has the advantage of also being appropriate for the difference between goals scored and goals conceded. Choice of methodology will depend on the specific objective being sought when studying the effect of HA on performance.